2011
DOI: 10.1136/aim.2010.002741
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Difference between the Effects of Single and Triple Indirect Moxibustion Stimulations on Skin Temperature Changes of the Posterior Trunk Surface?

Abstract: Objectives To determine whether any difference exists in responses to indirect moxibustion (IM) relative to thermal stimulation duration. Methods In experiment 1, 9 subjects attended two experimental sessions consisting of single stimulation with IM or triple stimulation with IM, using a crossover design. A K-type thermocouple temperature probe was fi xed on the skin surface at the GV14 acupuncture point. IM stimulation was administered to the top of the probe in order to measure the temperature curve. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…In normal warm moxibustion, thermal stimulation of the skin is inherently unstable because of the form and properties of the moxa, and quantitative stimulation is difficult to apply. 10,11 Therefore, the present study was performed with warm moxibustion-like thermal stimulation (WMTS) using an electronic warm moxibustion treatment appliance. The objective of the present study was to test the hypothesis that NO and/or PG contribute to cutaneous vasodilation during WMTS.…”
Section: Introductionmentioning
confidence: 99%
“…In normal warm moxibustion, thermal stimulation of the skin is inherently unstable because of the form and properties of the moxa, and quantitative stimulation is difficult to apply. 10,11 Therefore, the present study was performed with warm moxibustion-like thermal stimulation (WMTS) using an electronic warm moxibustion treatment appliance. The objective of the present study was to test the hypothesis that NO and/or PG contribute to cutaneous vasodilation during WMTS.…”
Section: Introductionmentioning
confidence: 99%
“…9 In this study we hypothesised that it would be more clinically applicable and effective when three acupuncture point locations were thermally stimulated rather than when the same duration of stimulation was applied on the same point. The changes in skin temperature observed following IM in this study suggest that multiple-point stimulation may produce a more profound impact on skin temperature than single-point stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, using the same type of IM, Mori et al found that the resulting human skin temperature ranged from 46°C to 67.5°C (mean 50°C). 9 A study by Yi investigated the thermal properties of a different type of IM in which moxa was placed on sliced garlic. 10 The study showed that the maximum temperature when the moxa was applied on a 1.7 mm garlic slice reached 43°C at the fi rst application, rising to 55°C during the fourth consecutive application.…”
Section: Introductionmentioning
confidence: 99%
“…17 20 A study by Adriaensen et al 21 showed that thermal stimulation of human skin at 44.5–46.5°C activated A-fibre mechano-heat-sensitive nociceptors. Mori et al 22 23 showed that the maximum temperature for indirect moxibustion was approximately 50°C.…”
Section: Introductionmentioning
confidence: 99%